The pricing of convertible debt offerings - Kang, Jun-Koo; Lee, Yul W. (Journal of Financial Economics, 1996)
We present the first empirical evidence on the pricing of convertible debt offerings. Using a sample of 91 convertible debt offerings from the period 1988–1992, we show a significant mean initial excess return of 1.11%. Our underpricing result is invariant to zero/nonzero coupons, maturity, issue size, or bond ratings. Further analysis reveals that various types of risk inherent in the new convertible issues are useful in explaining the cross-sectional variation in the initial excess returns. We offer an explanation for our results based on the arguments of the differential information model.